Nonna Maria and the case of the missing bride : a novel - Carcaterra, Lorenzo (Bantam Books, 2022)
"When a crime on a beautiful Italian island stumps the police, locals locals turn to the nosy, elderly widow Nonna Maria in this transporting mystery from author Lorenzo Carcaterra. Nonna Maria has lived in Ischia, a little island in the Gulf of Naples, her entire life. Recognizable by the widow's black she's worn every day for decades, Maria always has pasta on the stove and espresso in the pot for the neighbors who stop by to ask her advice on life and love. Everyone knows her, and she knows everyone's business. So when something goes wrong, islanders look to her, and not the local carabinieri, to find the solution. A man's fiancé disappears the night before the wedding. Is it a case of cold feet, or is something more sinister in play? A fisherman who knows the waters around the island like the back of his hand is drowned early one morning. Was it a tragic accident, or is there more to the story? While the police appear uninterested in these domestic concerns, Nonna Maria pours herself another glass of red wine and gets to work"--